Spatial binary coding method for stripe-wise phase unwrapping - Wang, Yuwei; Liu, Lu; Wu, Jun; Chen, Xiangcheng; Wang, Yajun (Applied optics. Optical technology and biomedical optics, 2020)
Binary coding methods have been widely used for phase unwrapping. However, traditional temporal binary coding methods require a sequence of binary patterns to encode the fringe order information. This paper presents a spatial binary coding (SBC) method that encodes the fringe order into only one binary pattern. Each stripe of the sinusoidal phase-shifting patterns is corresponding to an -bit codeword of the binary pattern. A robust stripe-wise decoding scheme is also developed to extract the -bit codeword, then fringe order can be determined, and stripe-wise phase unwrapping can be performed. Experiment results confirm that the SBC method can correctly recover the absolute phase of measured objects with only one additional binary pattern.